It's what you say and what you buy: A holistic evaluation of the corporate credit facilities - Nina Boyarchenko; Anna Kovner; Or Shachar (Federal Reserve Bank of New York, 2020)
We evaluate the impact of the Federal Reserve corporate credit facilities (PMCCF and SMCCF). A third of the positive effect on prices and liquidity occurred on the announcement date. We document immediate pass-through into primary markets, particularly for eligible issuers. Improvements continue as additional information is shared and purchases begin, with the impact of bond purchases larger than the impact of purchases of ETFs. Exploiting cross-sectional evidence, we see the greatest impact on investment grade bonds and in industries less affected by COVID, concluding that the improvement in corporate credit markets can be attributed both to announcement effects of Federal Reserve interventions on the economy and to the specific differential impact of the facilities on eligible issues.
Keywords: G12; G18; G19; 330; corporate credit facilities; bond liquidity; credit spreads; purchase effects